2000
DOI: 10.1046/j.1440-1614.2000.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

The Procedural Validity of Retrospective Case Note Diagnosis

Abstract: The procedural validity of diagnoses assigned via the application of checklists of operational criteria to case notes and clinical abstracts alone is unacceptably poor. Such sources need to be buttressed by other data, particularly direct patient interview and informant material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
1
10
0
Order By: Relevance
“…The present data are at variance with Mihalopoulos et al [29] . These authors reported substantially poorer agreement between diagnoses obtained by OPCRIT ratings, based upon clinical records, and diagnoses obtained by different clinical research instruments and checklists based upon research interviews compared with the concordance estimates between the different diagnoses obtained by interview data.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The present data are at variance with Mihalopoulos et al [29] . These authors reported substantially poorer agreement between diagnoses obtained by OPCRIT ratings, based upon clinical records, and diagnoses obtained by different clinical research instruments and checklists based upon research interviews compared with the concordance estimates between the different diagnoses obtained by interview data.…”
Section: Discussionsupporting
confidence: 85%
“…The discrepancy between their study and our study is most likely an effect of the different patient materials. Mihalopoulos et al [29] investigated patients with their fi rst episode of the illness, whereas the present study mainly consisted of patients treated for many years. Thus, the medical records in the present study are likely to be much more informative than the records analysed in the Australian study.…”
Section: Discussionmentioning
confidence: 99%
“…The mean kappa value from four studies (Azevedo et al ., ; Ekholm et al ., ; Mihalopoulos et al ., ; Vares et al ., ) was 0.72 (range 0.32–0.88, n = 392) indicating “substantial” agreement. One study reported several values for sensitivity and specificity the means of which were 0.98 and 1.00, respectively (Vares et al ., ).…”
Section: Resultsmentioning
confidence: 99%
“…The mean kappa across seven studies (Craddock et al ., ; Ekholm et al ., ; Isohanni et al ., ; Lazartigues et al ., ; Makikyro et al ., ; Mihalopoulos et al ., ; Vares et al ., ) was 0.60 (range 0.27–0.89, n = 605), indicating agreement at the top‐end of the “moderate” banding. The most commonly used classificatory system in these studies was DSM.…”
Section: Resultsmentioning
confidence: 99%
“…Although the OPCRIT is considered a reliable and well-validated tool, its design was primarily for extracting diagnostic information from case notes. Its use in retrospective data collection and as a mechanism for scaling symptom severity is open to challenge 15 and one cannot exclude the inadvertent biases introduced during the rating process. Two of the authors (S.N.S.…”
Section: Discussionmentioning
confidence: 99%